Experiências de pais e mães de crianças com deficiência: estudo comparativo entre múltiplas variáveis - Azevedo, Tássia Lopes de (2018)
In the family environment, individuals maintain their first interpersonal relationships with significant people, establishing important affective support for the development of each member. In this way, it is known that family is a privileged space for the development of the individual and of society. However, the birth of a disabled child can alter family relationships, and for many families there will be a need to undergo changes and adaptations. Considering the importance of families for child development and that parents of children with disabilities can experience parental experience in a differentiated way, this research aimed to identify and compare quality of life, resources, parental educational social skills, marital relationship, needs and social support, between parents and mothers of children with intellectual disability, physical disability, autism and delay in child development and correlate these variables. The research was developed with 120 participants, being 60 mothers and 60 parents. Participants were divided into four groups, each group being composed of 30 participants (15 fathers and 15 mothers). The groups were divided according to the diagnosis of children (intellectual disability, physical disability, autism and delayed child development). To collect data, the following instruments were used: Quality of Life Questionnaire "WHOQOL-bref"; Inventory of resources in the family environment; Script of Social Parenting Educational Skills Interview; Conjugal Relationship Questionnaire; Questionnaire on family needs and Social support questionnaire. These instruments contain quantitative data, which have been carried out measures of central tendency and dispersion. To compare the data of the parents and the mothers, from each group separately, the t-test was performed and the Pearson correlation test was used to relate the variables. The results showed that there were differences in at least one aspect related to quality of life, social educational parental skills, resources in the family environment, marital relationship, need and social support, when comparing fathers and mothers of children with intellectual disability, physical, autism and delayed neuropsychomotor development. As an exception, the items related to the follow-up and non-follow-up (G1, G2, G3 and G4), the daily activities of the child (G1, G3 and G4), the attitudes of the spouse who (G1 and G3) and social support (G4), which did not present statistically significant differences. The data suggest that the parents of children with disabilities experience their role in a different way, emphasizing that the interventions must meet the demands of the same considering their singularities. The correlations showed that the higher the parents' satisfaction with quality of life, marital relationship and social support, the smaller the family needs were, the higher the levels of social support were available, and the more skilled the parents could be. present in the parental and matrimonial relationship. It is concluded that the parental demands are modified depending on the deficiency and developmental delay that the child has. Thus, it is important to provide services, projects and programs that involve families and consider their real demands.